The interpersonal skills and leadership styles of supervisory librarians in U.P. Diliman - Resurreccion, Irene S.; Yang, Jackson V. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2001)
The objectives of this study are the following: 1) To determine the interpersonal skill level of supervisory librarians in U.P. Diliman; 2) To determine their different leadership styles; and 3) To determine the relationship of educational attainment and length of work experience to interpersonal skill.
This study focused on the interpersonal skill and leadership styles of 24 supervisory librarians in U.P. Diliman. Other respondents include, two to three staff of every supervisory librarians, his/her peers and his/her immediate Boss (Dean). A questionnaire was utilized to investigate the relationship between the independent variables, educational attainment and length of work experience and the dependent variable, interpersonal skill. It also determined the different leadership styles of the respective librarians with regards to different leadership concerns.
Through Analysis of Variance (ANOVA) and Kruskall - Wallis test using the Software Package for Social Sciences (SPSS), this study revealed that a majority of supervisory librarians in U.P. Diliman have a high interpersonal skill. Both ANOVA and Kruskall - Wallis Test revealed the interpersonal skill is not related to educational attainment and years of work experience. Other tests performed to validate earlier analysis are: Cramer's V. Pearson's R and Spearmans Correlation. Since supervisory librarians have high in interpersonal skills their skills should motivate and empower his/her staff for their continuing professional development. As well as their respective leadership styles should contribute to a more efficient library management.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: College librarians -- Philippines -- Quezon City; University of the Philippines Diliman libraries